2000
DOI: 10.1088/0953-8984/12/49/312
|View full text |Cite
|
Sign up to set email alerts
|

The photoluminescence emission in the 0.7-0.9 eV range from oxygen precipitates, thermal donors and dislocations in silicon

Abstract: There is a wide set of literature reports that suggest that over-coordinated oxygen or self-interstitials are, directly or indirectly, the chemical bridge between thermal donors, oxygen precipitates and dislocations, capable of supporting a common origin of their emission features in the 0.7-0.9 eV range. Finding the experimental proof of these suggestions was the aim of this present work, which required both appropriate preparation of samples and their careful optical, electrical and microscopical characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 29 publications
(46 reference statements)
2
22
0
Order By: Relevance
“…11) observed by Liesert et al [6]. If we consider that the P-line emission correspond to a radiative transition between a donor level at Ec-0.0015 eV and the deep trap at Ev+0.37 eV we could fit within few meV the P line emission energy at 0.767 eV, and conclude that the P luminescence originates from a transition from a OTD level to a deep level corresponding to a C-O complexes, as already proposed by some of us in a former article [3]. About the second issue, we have demonstrated that OTDs emit light at room temperature, although with a hundredfold decrease of intensity with respect to cryogenic temperatures.…”
Section: Czm Samplessupporting
confidence: 57%
See 1 more Smart Citation
“…11) observed by Liesert et al [6]. If we consider that the P-line emission correspond to a radiative transition between a donor level at Ec-0.0015 eV and the deep trap at Ev+0.37 eV we could fit within few meV the P line emission energy at 0.767 eV, and conclude that the P luminescence originates from a transition from a OTD level to a deep level corresponding to a C-O complexes, as already proposed by some of us in a former article [3]. About the second issue, we have demonstrated that OTDs emit light at room temperature, although with a hundredfold decrease of intensity with respect to cryogenic temperatures.…”
Section: Czm Samplessupporting
confidence: 57%
“…In fact, while it is well known that oxygen rich silicon annealed at 450 'C for several hours exhibits a prominent photoluminescence spectrum with a narrow no-phonon line at 0.767 eV, generally labelled P line [2], a direct proof that oxygen is incorporated in the centre has not yet been given. Furthermore, PL measurements have cast doubts on a simple relationship between thermal donors and the P line [3]. Eventually, a carbon isotopic effect experimentally determined in the P line shows a possible involvement of carbon-oxygen complexes in the defect involved in the P line luminescence [2].…”
Section: Introductionmentioning
confidence: 99%
“…They also observed pairwise similarity between D1/D2 and D3/D4 regarding their spatial distribution. Oxygen precipitates has also been found to be a possible origin of the D-lines by Pizzini et al 10 and Tajima et al 11 Arguriov 12 proposed D1 and D2 to be generated by transitions between one-dimensional bands on 60…”
Section: B D-linesmentioning
confidence: 96%
“…In the samples with high oxygen concentrations [O i ∼10 18 cm -3 ] the additional band is generally shifted to the high energy side from D1 line. The maximum position of this band is not constant and depends on high temperature treatment in a non-monotone way [11]. Thus one can conclude that during plastic deformation the process of oxygen gettering by dislocations takes place, which leads to a gradual transformation of DRL.…”
Section: Introductionmentioning
confidence: 92%